Ground heating and methane oxidation processes at shallow depth in Terre Calde di Medolla (Italy): Numerical modeling. Issue 5 (19th May 2015) - Nespoli, Massimo; Todesco, Micol; Capaccioni, Bruno; Cremonini, Stefano
Abstract The area known as Terre Calde (literally "hot lands") in the plain of the Po River (Italy) is well known for unusual ground temperatures, and up to now, the cause o/f the heating has not been fully investigated. These higher‐than‐average temperatures are commonly associated with diffuse methane seepage. A detailed study of shallow stratigraphy, temperature profile, and associated gas concentrations and flow rates recently suggested that the observed anomaly could be related to the exothermic oxidation of biogenic methane, possibly rising from a shallow peat layer. In this work, a porous media flow simulator (Transport of Unsaturated Groundwater and Heat 2) was applied to verify a conceptual model of this phenomenon. The model describes a layered system, with a shallow unsaturated zone, where methane is continuously supplied along the base and heat is generated as a result of its oxidation above the water table. To mimic the oxidation process, heat sources are placed within the layer where oxidation takes place, and the heat generation is computed as a function of methane flux entering the layer. Numerical simulations were carried out imposing different methane flow rates along the base of the model. The simulations also explored the efficiency of methane oxidation, considering different heat generation rates and accounting for seasonal effects. The good match between observed and simulated temperature profiles suggests that the main features of the process are captured by the model and that the conceptual model devised on the base of available data is plausible from a physical point of view.